Faktor-faktor yang Mempengaruhi Profitabilitas Bank Syariah di Asia Pasifik Tahun 2010-2016 - Haryadi, Anton (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2022)
The purpose of this study is to examine the impact of several factors, namely Capital Adequacy Ratio (CAR), Bank Size, Technology (Internet Banking), and Gross Domestic Product (GDP) on the profitability or Return On Asset (ROA) of Islamic banks operating in the Asia Pacific region between 2010-2016. The sample consists of six Islamic banks located in this region. Data for the variables "Capital Adequacy Ratio" and "Bank Size" were obtained from the annual financial statements provided by the six banks. The variable "Technology" was measured using dummy variables, while the data for the variable "Gross Domestic Product" was obtained from the financial statements of each country. The Ordinary Least Square method was used in Eviews 8 software for analysis. The results show that only the Bank Size variable shows a significant positive effect on ROA with a significance value of 0.0000. In contrast, CAR has a coefficient value of 0.1085, indicating no significant impact on ROA. Similarly, Internet Banking technology and GDP show insignificant coefficients with values of 0.6561 and 0.3057 respectively. Furthermore, when considering the four factors simultaneously - CAR, Bank Size, Technology (Internet Banking), and GDP - it can be concluded that the four factors jointly exert an influence on ROA based on the F-calculated value that exceeds the F-table i.e. 5.569962 > 2.626052285, which is supported by the probability value that is smaller than α = 0.05 i.e. 0.000127 < α = 0.05. The adjusted R-squared value is determined to be around 50%, which indicates that about half of the variation in Return On Assets can be explained by variations in Capital Adequacy Ratio (CAR), Bank Size, Technology (Internet banking), and Gross Domestic Product (GDP).